PROPHET’S PERSONALITY: A LEADERSHIP AND MANAGERIAL STUDY OF THE PROPHET MUHAMMAD PBUH - imam ahfas (AT-THARIQ: Jurnal Studi Islam dan Budaya, 2023)
This article examines the managerial role of Prophet Muhammad in his position as a leader. The method used in this research is descriptive-qualitative and is included in the literature review. The process of collecting data in this study is by making observations, in the sense of tracking various references related to the study’s focus, both from books, articles, and so on, that support these data. The data analysis technique used in this study is the content analysis method. The study shows that almost all leadership theories exist in Muhammad PBUH, for example, four leadership functions developed by Stephen Covey: 1. pathfinding; 2. aligning; 3. empowering and; 4. modeling. Likewise, the characteristics of Muhammad PBUH can also be found in the basic characteristics of leadership according to Warren Bennis (1994) in “On Becoming a Leader,” among others: 1. Visionary (guiding vision); 2. Strong-willed (passion); 3. Integrity; 4. Trust; 5. Curiosity, and; 6. Courage. Likewise with management theory, according to G. R. Terry, the management process is Planning, Organizing, Actuating, and Controlling, all of which are in Muhammad PBUH